“Estudio comparativo entre el procedimiento abreviado y el procedimiento ordinario en la legislación ecuatoriana”. - Orozco Díaz, Rafael Stefano (2017)
This job has been divided in four parts. The first parts contain introduction, the reason why I decided work in this topic; the way to post and justify the importance of this investigation. In this chapter I could explain the reason why is important for lawyers and general peopling this original job. In the second part of this investigation we find a little story and basic definitions for understand our principal goal. This chapter talks about similar previously jobs and what people think about this two process. In this part we also can find two comparative tables. The first one is about similarities and differences between “Procedimiento Abreviado” and “Procedimiento Ordinario”; and the second one is about the different time of pain in the judgment in all the crimes which have the possibility to negotiate the pain. This two tables are important for us because with them we can appreciate in a better way the advantages and disadvantages of this process. The third parts talks about the methodology which was used for obtain results and information about this investigation job. The methods the investigator used was qualitative, deductive, analytical, historical, descriptive, explanatory, longitudinal and comparative. After of this, and as a finally chapter we can watch the results of the principal discussion in a summary of conclusions and recommendations for lawyers, accuser and defenders; for judges and for general people.